Effects on Funding Equity of the Arizona Tax Credit Law - Glen Y. Wilson (Arizona State University, 2000)
This article examines the results from the first year (1998) of the Arizona Education Tax Credit program. The tax credit law allows individuals a dollar- for-dollar tax credit of $500 for donations to private schools and a dollar-for-dollar tax credit of $200 for donations to public schools. Although one justification for this statute was that it would help lower income students, the primary beneficiaries of this program tend to be the relatively well off. The author concludes that Arizona's tax credit law increases educational funding inequity in Arizona. Data for 1999, only recently made available, show a 159.1 percent increase in total contributions and an exacerbation of the trends noted here.